Curriculum Management in Madrasah Aliyah Islamic Boarding Schools to Enhance Character Education - Mardiana Mardiana; Rusydi Ananda; Muhammad Rifa'i (Journal of General Education and Humanities, 2025)
This study investigates the practices of curriculum management in Madrasah Aliyah (Islamic Senior High School) within two Islamic boarding schools in Batu Bara Regency, namely, Jabal Hindi and Al-Mukhlishin. These institutions were selected due to their strong commitment to integrating academic excellence with character education. Using a qualitative approach with a multi-site study design, the research explores in depth the curriculum planning, implementation, and evaluation processes within the unique cultural and religious setting of Islamic boarding schools. Special attention is given to how character values rooted in Islamic teachings are integrated into both formal classroom instruction and non-formal learning activities. The study examines the organizational and instructional strategies adopted by each school and the roles of key stakeholders, including principals, teachers, kyai (spiritual leaders), administrators, and students. It identifies various supporting factors that contribute to effectively implementing a character-based curriculum, such as visionary leadership, a conducive learning environment, teacher professionalism, and a strong institutional culture. At the same time, it highlights several inhibiting factors, including limited infrastructure, diverse student backgrounds, and challenges related to digital media exposure that may conflict with Islamic values. In addition, this research uncovers several innovative practices the schools use to strengthen character education, including project-based learning, thematic integration across subjects, spiritual mentoring, and digital tools such as e-portfolios to monitor student progress.